2007
DOI: 10.1681/asn.2007020256
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease, Cardiovascular Events, and the Effects of Perindopril-Based Blood Pressure Lowering

Abstract: Chronic kidney disease (CKD) is associated with a high risk of cardiovascular disease, but evidence regarding the effectiveness of interventions to reduce that risk is lacking. The Perindopril Protection against Recurrent Stroke Study (PROGRESS) study enrolled 6105 participants with cerebrovascular disease and randomly allocated them to perindopril-based blood pressure-lowering therapy or placebo. Individuals with CKD were at approximately 1.5-fold greater risk of major vascular events, stroke, and coronary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 26 publications
1
56
0
6
Order By: Relevance
“…The Treating to New Targets Study, a subanalysis of individuals with known coronary heart disease and CKD, reported that, with respect to major cardiovascular events, treatment with atorvastatin 80 mg yielded an NNT of 24 over 5 years. 8 In the Perindopril Protection against Recurrent Stroke Study, among individuals with known cerebrovascular disease and CKD, perindoprilbased BP therapy yielded an NNT of 11 over 5 years with respect to major vascular events 18 ; similarly, a study of individuals post-MI with heart failure and CKD from the Survival and Ventricular Enlargement study reported that treatment with captopril yielded an NNT of 9 over 3.5 years with respect to major cardiovascular events. 19 After a series of trials that included large portions of individuals receiving dialysis, the benefit of statin-based therapies as eGFR declines (particularly to the point of requiring RRT) was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The Treating to New Targets Study, a subanalysis of individuals with known coronary heart disease and CKD, reported that, with respect to major cardiovascular events, treatment with atorvastatin 80 mg yielded an NNT of 24 over 5 years. 8 In the Perindopril Protection against Recurrent Stroke Study, among individuals with known cerebrovascular disease and CKD, perindoprilbased BP therapy yielded an NNT of 11 over 5 years with respect to major vascular events 18 ; similarly, a study of individuals post-MI with heart failure and CKD from the Survival and Ventricular Enlargement study reported that treatment with captopril yielded an NNT of 9 over 3.5 years with respect to major cardiovascular events. 19 After a series of trials that included large portions of individuals receiving dialysis, the benefit of statin-based therapies as eGFR declines (particularly to the point of requiring RRT) was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, ACE inhibitor-based treatment has been associated with reduced risk of major vascular events among patients with CKD, although the effect of BP differences between the groups is unclear (23,24). Other studies indicate that, independently of the BP-lowering effect, no antihypertensive drug class has significant advantages over others in preventing stroke in CKD patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…This magnitude of change in SBP is predicted to result in a risk reduction of 4 to 5% on the basis of previous observational studies. [45][46][47] In this trial, the secondary renal outcome (dialysis or doubling of SCr) was similar in the telmisartan and ramipril groups but occurred more frequently with combination therapy. Combination therapy did reduce proteinuria to a greater extent than monotherapy but overall significantly worsened major renal outcomes.…”
mentioning
confidence: 99%